Highly permeable innovative PDMS coated polyethersulfone membranes embedded with activated carbon for gas separation - Haider, Bilal; Dilshad, Muhammad Rizwan; Ur Rehman, Muhammad Atiq; Akram, Muhammad Sarfraz; Kaspereit, Malte (Journal of Natural Gas Science and Engineering, 2020)
Innovative asymmetric polyethersulfone (PES) membranes embedded with activated carbon (AC) were synthesized and then surface coated with thin PDMS layer. The membranes were then tested with advanced analytical techniques like FTIR, TGA, SEM and EDX analysis. Thereafter, the membranes were tested for gas permeation analysis with following five gases: carbon dioxide, hydrogen, nitrogen, helium and methane. The effects of embedding AC and feed gas pressure on gas permeation properties were also examined. The permeance of all the gases improved with the embedding of AC in the membrane without much decreasing their ideal selectivity while PDMS coating enhanced the ideal selectivity at the expense of decreasing permeance of all the gases. It was found that 30 wt. % AC embedded PDMS coated PES membrane, having thickness of 80 μm, exhibited the best gas permeation properties for following five pair of gases CO2/N2, CO2/CH4, H2/N2, He/N2 and He/CH4 at 25 °C and 20 bar. The best performing membrane was also tested for long term stability by exposing it with each gas for 96 h. It was also found that the performance of 30 wt % AC embedded membrane, surpassed the 2008 Robeson trade off line for all pair of gases except for CO2/CH4 for which it nearly touched this line. Finally, PDMS coated membranes were also tested with CO2/CH4 (50:50) mixture at high pressure and found that mixed gas permeation properties are considerably lesser than pure gas permeation properties due to possibility of competitive sorption phenomenon between the gases.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Activated carbon; Gas separation membranes; PDMS coating; Polyethersulfone